2018
DOI: 10.9734/cjast/2018/40193
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, Functional and Sensory Properties of Vegetable Oil Blends

Abstract: Blending vegetable oils can be one of the potential solutions for optimum fatty acids composition and good storage stability. The present study was conducted to identify the best oil blend ratio in terms of physico-chemical, functional and sensory properties of cottonseed and soyabean oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Consistent values showed that the oil blend is stable. However, in a study of soybean and cottonseed oil blends, it was reported that specific gravity of blends decreases due to the reduction of mass of oil and hence density as temperature increases (Prathibha et al, 2018).…”
Section: Refractive Indexmentioning
confidence: 99%
“…Consistent values showed that the oil blend is stable. However, in a study of soybean and cottonseed oil blends, it was reported that specific gravity of blends decreases due to the reduction of mass of oil and hence density as temperature increases (Prathibha et al, 2018).…”
Section: Refractive Indexmentioning
confidence: 99%
“…Blend containing cottonseed and palm olein oils in the ratio of 50:50 showed 2.27% increment in the content of polymeric compounds after 10 h of frying as compared to 12.10% and 11.40% increments in case of pure cottonseed and pam olein oils, respectively (Arslan et al, 2017). Blend of soybean oil with cottonseed oil (80:20) showed low peroxide value (12.16 meq/Kg) as compared to unblended soybean oil (42.30 meq/Kg) indicating higher oxidative stability of the blends (Prathibha et al, 2018). The oxidative stability of the blended oils is discussed in detail in Section 4.1.…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…Oil having smoke point above 200°C is recommended to be ideal for frying. Prathibha et al (2018) blended cottonseed oil and soybean oil in different ratios and found that the smoke point of all the blends was above 200°C. Owing to its high smoke point, rice bran oil improves the oxidative stability of less stable cooking oils when blended in appropriate proportion and thereby increases the suitability of the blend for deep frying.…”
Section: Properties Of Vegetable Oils Formulated By Blendingmentioning
confidence: 99%
“…These results are in agreement with Hashem et al, (2017);Sabir Hasan. et al, (2016); Prathibha et al, (2018) and Tilahun Mengistie et al, (2018).…”
Section: Data In Tablementioning
confidence: 99%